2003
DOI: 10.1007/s00246-002-0120-9
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Term Effect of Epoprostenol on Severe Portopulmonary Hypertension

Abstract: We examined the effect of continuous intravenous infusion of epoprostenol (35 ng/kg/min) on severe portopulmonary hypertension caused by biliary atresia. Pulmonary hemodynamics improved and brain natriuretic peptide and human atrial natriureic peptide decreased to normal values during epoprostenol therapy. However, the improvement in pulmonary hemodynamics was not sufficient to permit liver transplantation. Our patient was obliged to stop epoprostenol therapy because of financial problems and epoprostenol was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Only small retrospective studies have reported positive effects on functional status and hemodynamics in those patients. [34][35][36][37][38] The major limiting factor of epoprostenol is its mode of administration which requires continuous intravenous infusion through a tunneled central venous catheter, exposing patients to important complications, including bleeding at the time of catheter insertion, and a perpetual risk of local and/or bloodstream infections.…”
Section: Prostanoidsmentioning
confidence: 99%
“…Only small retrospective studies have reported positive effects on functional status and hemodynamics in those patients. [34][35][36][37][38] The major limiting factor of epoprostenol is its mode of administration which requires continuous intravenous infusion through a tunneled central venous catheter, exposing patients to important complications, including bleeding at the time of catheter insertion, and a perpetual risk of local and/or bloodstream infections.…”
Section: Prostanoidsmentioning
confidence: 99%
“…Portopulmonary hypertension is a more severe and less common pulmonary complication that has been observed in children with biliary atresia 73–84. Most of the reports of portopulmonary hypertension are anecdotal and are often associated with a fatal outcome.…”
Section: Portopulmonary Hypertensionmentioning
confidence: 99%
“…This relative hypoxia may complicate an already diseased pulmonary vasculature, accelerating the appearance of symptoms. However, hypoxia is not a required stimulus for the development of PPHTN in children, because PPHTN has been described at sea level, 29 and 1 of our 7 patients developed PPHTN while living at sea level.…”
Section: Discussionmentioning
confidence: 76%